An enquiry to the role of CB1 receptors in neurodegeneration - Ignacio Fernández-Moncada; Abel Eraso-Pichot; Tommaso Dalla Tor; Bérénice Fortunato-Marsol; Giovanni Marsicano (Neurobiology of Disease, 2023)
Neurodegenerative disorders are debilitating conditions that impair patient quality of life and that represent heavy social-economic burdens to society. Whereas the root of some of these brain illnesses lies in autosomal inheritance, the origin of most of these neuropathologies is scantly understood. Similarly, the cellular and molecular substrates explaining the progressive loss of brain functions remains to be fully described too. Indeed, the study of brain neurodegeneration has resulted in a complex picture, composed of a myriad of altered processes that include broken brain bioenergetics, widespread neuroinflammation and aberrant activity of signaling pathways. In this context, several lines of research have shown that the endocannabinoid system (ECS) and its main signaling hub, the type-1 cannabinoid (CB1) receptor are altered in diverse neurodegenerative disorders. However, some of these data are conflictive or poorly described. In this review, we summarize the findings about the alterations in ECS and CB1 receptors signaling in three representative brain illnesses, the Alzheimer's, Parkinson's and Huntington's diseases, and we discuss the relevance of these studies in understanding neurodegeneration development and progression, with a special focus on astrocyte function. Noteworthy, the analysis of ECS defects in neurodegeneration warrant much more studies, as our conceptual understanding of ECS function has evolved quickly in the last years, which now include glia cells and the subcellular-specific CB1 receptors signaling as critical players of brain functions.